Hysteretic behavior and strength capacity of shallowly embedded steel column bases with SFRCC slab. (Earthquake engineering & structural dynamics.)
A series of shallowly embedded steel column bases consisting of an exposed column base and a floor slab is tested under horizontal cyclic loading to very large deformation. The effects of floor slabs on strength and ductility are examined using concrete and Steel fiber-reinforced cementitous composites (SFRCC) for the floor slab. The elastic stiffness, maximum strength, and dissipated energy of the column bases when they include SFRCC increase by 40, 70 and 70 percent over those of corresponding column bases with concrete floor slab. Better bonding behavior is notable for SFRCC, and the maximum strength and dissipated energy further increase by 15-30 percent and 70-90 percent, respectively, owing to the careful arrangement of reinforcing bars. Numerical models are developed to enhance the understanding the behavior of shallowly embedded column bases. Procedures for estimating the elastic stiffness and maximum strength of shallowly embedded column bases with conventional concrete are calibrated for their applicability to those with SFRCC slab.